The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40520-017-0827-3
|View full text |Cite
|
Sign up to set email alerts
|

Colistin nephrotoxicity in the ICU: Is it different in the geriatric patients?

Abstract: In our study, in geriatric patient group colistin nephrotoxicity was not different from the younger age group. In the ICU, the age for nephrotoxicity does not appear to be a point to be considered for the initiation of colistin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
6
2
2
Order By: Relevance
“…Although some studies demonstrated higher mortality in patients with COL nephrotoxicity, others showed no difference (3,19,20).Özkarakaş et al reported similar mortality rates between patients with and without nephrotoxicity (19). In another study comparing mortality rates in older and young adult patients receiving COL, there was no difference between the two groups (5). In contrast to these findings, mortality rates were statistically higher in the nephrotoxicity group and in the geriatric nephrotoxicity subgroup in our study.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Although some studies demonstrated higher mortality in patients with COL nephrotoxicity, others showed no difference (3,19,20).Özkarakaş et al reported similar mortality rates between patients with and without nephrotoxicity (19). In another study comparing mortality rates in older and young adult patients receiving COL, there was no difference between the two groups (5). In contrast to these findings, mortality rates were statistically higher in the nephrotoxicity group and in the geriatric nephrotoxicity subgroup in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…Aydogan et al reported higher rates of cardiac disease and COPD in the geriatric group but it was found that advanced age is not a risk factor for nephrotoxicity. (5). In our study, no significant difference was found between geriatric and young patients who developed nephrotoxicity in terms of underlying chronic diseases, concomitant nephrotoxic agent use, initial serum urea and creatinine values.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The rise and dissemination of multidrug-resistant (MDR) Enterobacteriaceae, especially carbapenem-resistant Enterobacteriaceae (CRE), with mechanisms such as NDM-1, KPC, and OXA-48/181 in the last few decades have led to urgent challenges in the clinical treatment of MDR or extensively drug-resistant (XDR) pathogen diseases (1, 2). In this case, despite having a side effect of nephrotoxicity, colistin is still considered a last-resort antibiotic in the clinical treatment of serious infections caused by CRE (3). However, mobile colistin resistance (MCR), referring to a plasmid-mediated gene encoding a phosphoethanolamine transferase conferring resistance to colistin, was initially reported in 2015 in China and named mcr-1 ( m obile c olistin r esistance 1) (4).…”
Section: Announcementmentioning
confidence: 99%